Caracterización morfo-agronómica de dieciséis accesiones de fréjol voluble (Phaseolus vulgaris l) colectadas en el cantón Chillanes, provincia Bolívar - Agualongo Tixi, Gabriel Vinicio (2021)
Beans occupy the eighth place among the legumes, most planted on the planet; it is one of the most important due to its wide distribution in the five continents and therefore, one of the highest consumption in Central and South America. In Ecuador, beans are consumed fresh and dry and as a raw material for agribusiness. The production of voluble beans is related to the high incidence of diseases, which are aggravated by the widespread use of susceptible seed, which requires a high use of pesticides for its management with negative consequences, high exposure and risk of workers to poisoning and contamination of the environment. The morpho-agronomic characterization of sixteen accessions of voluble bean (Phaseolus vulgaris L) collected in the Chillanes canton, Bolívar province; had as objectives i) To determine the morpho-agronomic characteristics of sixteen accessions of voluble beans. ii) Select the best accessions of voluble beans for this agro-ecological zone. iii) Create a database of the morpho-agronomic characterization of sixteen accessions of voluble beans for this agro-ecological zone. A randomized complete block experimental design with 3 replications was used. The treatments were: T1: Canary Short Sheath (Cream); T2: Long Pod Canary (Yellow); T3: Canary Long Sheath Yellow Hilium Black; T4: Short Sheath Primary Color Cream Secondary Color White; T5: Pale Cream; T6: Short Pod Canary (Collection No. 5); T7: Short Pod Canary (Collection No. 1); T8: Black Hilium Kidney Canary; T9: Flattened Kidney Cream Bay; T10: Round White; T11: UEB Bombolim Solid Red Round; T12: Voluble Black - Cream Oblong Shape; T13: Voluble Cream - Black Oblong Shape; T14: Red Speckled Oblong Cargo Mantle; T15: Cream Oblong Bayo and T16: INIAP 426 Canario Seven Colinas. Was carried out Analysis of variance, Tukey test at 5%, to compare averages of accessions of voluble beans. Correlation analysis and lineal regression. The results obtained are: The 16 voluble bean accessions presented different morpho-agronomic characters. The highest yield of young beans was given in treatment T7: Canario Vain Corta (Collection No. 1) with 17.975,92 Kg / ha. The accession with the best dry grain yield was T3: Canary Long Pod Yellow Hilium Negro 3.382,13 Kg / ha. The agronomic components that increased the dry bean yield at 13% humidity were plant height; polar diameter of the grain; grain weight per plant and bean yield in tender pod. The fickle bean germplasm evaluated showed Medium Resistance for Anthracnose (Colletotrichum lindemuthianum), Roya (Uromyces appendiculatus) and Ascoquita (Phoma exigua). The T1 voluble bean accessions were selected: Canario Vaina Corta (Cream); T3: Canary Long Sheath Yellow Hilium Black; T5: Pale Cream; T6: Short Pod Canary (Collection No. 5); T7: Short Pod Canary (Collection No. 1); T12: Voluble Black - Cream Oblong Shape; T13: Voluble Cream - Black Oblong Shape, due to its agronomic and morphological characteristics, resistance to the complex of foliar diseases.